Repair of Damaged Circular Hollow Sectional Steel Beam by Carbon Fiber Reinforced Polymer Patch - SETVATI, MAHDI RAZAVI (2018)
The issue of rehabilitation of the structural infrastructure, such as offshore structure and bridge, is one of the primary interests in civil engineering community. The superior mechanical properties and durability of carbon fiber reinforced polymer (CFRP) materials make them promising materials to repair steel structures.